2021
DOI: 10.3390/nu13072300
|View full text |Cite
|
Sign up to set email alerts
|

Acute Administration of Bioavailable Curcumin Alongside Ferrous Sulphate Supplements Does Not Impair Iron Absorption in Healthy Adults in a Randomised Trial

Abstract: Ferrous sulphate (FS) is a cost effective, readily available iron supplement for iron deficiency (ID). The pro-oxidant effect of oral ferrous iron is known to induce inflammation, causing gastric side-effects and resulting in poor compliance. Curcumin is a potent antioxidant and has also been shown to exhibit iron chelation in-vitro, although it is not established whether these effects are retained in-vivo. The aim of this study was therefore to assess the influence of a formulated bioavailable form of curcumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…We recently demonstrated that HydroCurc™ does not adversely affect oral ferrous sulphate absorption in a human RCT [ 43 ], therefore, any difference in systemic biological responses/biomarkers in the current study are unlikely to be caused by the availability or levels of serum iron between treatment groups. Taken together, the results suggest that the presence of curcumin in combination with iron leads to the majority of the observed decreases in inflammation-related markers, compared to iron alone.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We recently demonstrated that HydroCurc™ does not adversely affect oral ferrous sulphate absorption in a human RCT [ 43 ], therefore, any difference in systemic biological responses/biomarkers in the current study are unlikely to be caused by the availability or levels of serum iron between treatment groups. Taken together, the results suggest that the presence of curcumin in combination with iron leads to the majority of the observed decreases in inflammation-related markers, compared to iron alone.…”
Section: Discussionmentioning
confidence: 82%
“…Whole turmeric is known to have similar effects in humans, with 20–90% reduction in iron absorption [ 42 ]. Although the mechanisms of iron and curcumin interaction and their effect on the human physiology are not yet well understood, a recent study showed that a formulated bioavailable form of curcumin had no negative impact on acute iron absorption [ 43 ]. This formulation (HydroCurc™) consisted of 80% curcumin, 17% demethoxycurcumin (DMC), and 3% bisdemethoxycurcumin (BDMC), ~85% total curcuminoids, entrapped in a patented delivery system (LipiSperse ® ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that acute administration of bioavailable curcumin alongside Ferrous Sulphate supplements does not impair iron absorption thereby helping in tackling anaemia in RA patients. [38] The RBC count performed on 0, 1 st , 3 rd , 7 th , 14 th , 21 st , 28 th days suggests that ferrous sulphate was efficient in increasing the RBC count of the male Wistar rats. Also, the combination group showed a comparatively increase RBC count than the standard suggests that it could be used for better management of RBC levels in the blood of arthritic patients.…”
Section: Discussionmentioning
confidence: 92%
“…Another study showed that Theracurmin enhanced the absorption of curcumin compared to curcumin powder in healthy adults . Several other studies involving the administration of curcumin and its formulations in healthy humans also showed high absorption and bioavailability. ,, Moreover, curcumin supplementation in combination with ferrous sulfate was shown to enhance serum levels of iron, total iron binding capacity, and hemoglobin in healthy subjects . Furthermore, the administration of curcumin to healthy patients was found to be safe and well tolerated. ,, The health-promoting effect of the curcumin formulation Longvida was evaluated in healthy middle-aged individuals.…”
Section: Clinical Trials Of Turmeric and Curcuminmentioning
confidence: 99%
“…59,126,144−151 Moreover, curcumin supplementation in combination with ferrous sulfate was shown to enhance serum levels of iron, total iron binding capacity, and hemoglobin in healthy subjects. 152 Furthermore, the administration of curcumin to healthy patients was found to be safe and well tolerated. 45,128,153−155 The healthpromoting effect of the curcumin formulation Longvida was evaluated in healthy middle-aged individuals.…”
Section: Clinical Trials Of Turmeric and Curcuminmentioning
confidence: 99%